An Evaluation of Cost Optimization Strategies for BRT Projects in Pakistan - Khan, F.; Ahmed, A.; Ahmed, M.; Baig, M. A. U. (Engineering, Technology & Applied Science Research, 2022)
In developing countries like Pakistan, economic instability, improper planning, non-optimal design, delays in construction, and unsustainability during the operations of transportation megaprojects cause an unnecessary burden on the national exchequer. Recently, several Bus Rapid Transit (BRT) projects have been initiated in Pakistan. The detailed evaluation of the cost and capacity of BRT projects in Pakistan revealed that their cost could have been optimized. This research evaluated the first BRT project in Karachi for potential cost optimization through proper alignment of the BRT. One of the major segments of the Green-Line BRT from Surjani to Nagan was evaluated, which is presently designed as an elevated section. Other possible options such as curb-side, two-way side, and median alignments were explored in detail. The study showed that the cost of this section could have been reduced from the existing USD 75 million to USD 61 million by providing a two-way side aligned or curb-side aligned BRT infrastructure without affecting existing capacity. This case study shows that it is necessary to critically evaluate all the possible options while planning and designing transportation megaprojects.